Regulatory T-cell deficiency leads to pathogenic bullous pemphigoid antigen 230 autoantibody and autoimmune bullous disease - Häberle, Stefanie; Wei, Xiaoying; Enk, Alexander; Hadaschik, Eva (The journal of allergy and clinical immunology, 2018)
Background - Autoimmune bullous diseases/dermatoses (AIBDs) are severe autoantibody-mediated skin diseases. The pathogenic relevance of autoreactive CD4+ T cells for the induction of autoantibody production remains to be fully evaluated. Scurfy mice lack functional regulatory T (Treg) cells, experience spontaneous activation of autoreactive CD4+ T cells, and display severe erosive skin lesions suggestive of AIBDs. - Objective - We sought to determine whether AIBDs develop in Treg cell-deficient scurfy mice. - Methods - Histology, indirect immunofluorescence (IF) microscopy, direct IF, and ELISA were used to prove the presence of AIBDs in scurfy mice. Monoclonal autoantibodies from sera of scurfy mice were screened by using indirect IF on murine skin, and immunoprecipitation and mass spectrometry were used for target antigen identification, followed by confirmation in modified human embryonic kidney cells and murine keratinocytes. Pathogenicity was determined by injecting the autoantibody into neonatal mice and transferring scurfy CD4+ T cells into nu/nu mice. - Results - Autoantibodies against different known autoantigens of AIBDs spontaneously develop in scurfy mice. Histology reveals subepidermal blisters, and direct IF of skin of scurfy mice shows a predominant linear staining pattern. The mAb 20B12 shows a linear staining pattern in indirect IF, recognizes the murine hemidesmosomal protein bullous pemphigoid antigen 230 (BP230) as the target antigen, and cross-reacts with human BP230. Purified mAb 20B12 induces subepidermal blisters in neonatal mice. Transfer of scurfy CD4+ T cells is sufficient to induce antibodies with reactivity to AIBD autoantigens and subepidermal blisters in the skin of recipient T cell-deficient nu/nu mice. - Conclusion - We show that the absence of Treg cells leads to AIBDs by pathogenic autoantibodies targeting BP230.